The Music of the Catholic and Hindu Gaudde: Voicing the Unheard through Heritage - Pereira, Cláudia (Goa 2011: Reviewing and Recovering Fifty Years, 2014)
My main thrust is that the dances and songs of the Catholic Gaudde performed in specific religious rituals, formerly repressed during the Portuguese colonialism for not being Catholic and considered as heretic are nowadays repositioned under the marketing of tourism as an authentic cultural form of Goa’s heritage that resisted its colonial past. The Gaudde, an unprivileged social group, therefore, use the historical past in Goa to show their previous invisible resistance to the Portuguese governors, a lesser known aspect of colonialism in Goa. The Gaudde transformed the memory of their colonial resilience as Goan heritage, marketing it as pre-Portuguese. To this day, their Catholic dharma encompasses dances and music that are still similar to those of the Hindu Gaudde—the group they belonged to before they converted to Christianity—and so the words of their songs must be interpreted in the light of Hindu ritual logic, albeit the names of gods have been replaced by those of Christian saints, to whom they pray.